The Impact of Pollution on the Nematode and Harpacticoid Copepod Species Composition of an Estuarine Mudflat - Mohd Long, Shabdin (1990)
A study was carried out in the Forth estuary (Scotland) to determine the impact of industrial effluents on the nematodes and harpacticoid copepods species of an estuarine mudflat. The nematodes and harpacticoid copepods species in the area ranging from the species which are absent from the vicinity of the effluents to the species which occure predominantly in the most highly polluted sediments display a spectrum of responses to the discharges. It is thought at least some of the species favouring the immmediate vicinity of the effluent channels would be associated with the dense microalgal mat that fringes the channels. Two factors seemed to be dominant in controlling the species distribution of nematodes and harpacticoid copepods in the area interdal height and pollution. Cluster analysis of the species abundance data from the sampling stations "clearly showed the separation of sites on the upper, middle and lower shore. The ordination of the stations was also strongly influenced by intertidal height superimposed by pollution.